Foundation for adaptive charging solutions: Optimised use of electric vehicle charging capacity. Issue 6 (1st September 2021) - Simolin, Toni; Rauma, Kalle; Rautiainen, Antti; Järventausta, Pertti; Rehtanz, Christian
Abstract: As electric vehicles (EVs) are emerging, smart and adaptive charging algorithms have become necessary to ensure safe and efficient operation of the grid. In the scientific literature, most of the proposed charging control algorithms focus solely on EV usage‐related behaviour, while the charging characteristics of EVs are overlooked. Herein, realistic charging characteristics are illustrated and discussed. More notably, to overcome the issues caused by the non‐idealities in charging characteristics, a new adaptive charging characteristics expectation algorithm is proposed. The objective of this algorithm is to enable accurate estimation of the non‐ideal charging characteristics. This can be used to reallocate any unused charging capacity and to ensure that the intended total capacity is used effectively. The effectiveness of the proposed algorithm is demonstrated using hardware‐in‐the‐loop simulations with commercial EVs and real charging data. The results show that the proposed algorithm achieves an 88%–97% capacity usage rate, while the current benchmark solution achieves only 45%.